THE GLOBAL RELLEX: TOWARD A TRANSNATIONAL TURN IN EVANGELICAL HISTORIOGRAPHY. - Gehrz, Christopher (Fides et historia, 2015)
The article comments on David R. Swartz's book "Moral Minority: The Evangelical Left in an Age of Conservatism." It describes the important role played by the Peruvian theologian Samuel Escobar and his colleagues in developing an international conservation on issues that include evangelism, social justice, and cultural captivity. It also explores the progress toward a transnational turn in evangelical historiography.